Words across History: Advances in Historical Lexicography and Lexicology - Domínguez Rodríguez, María Victoria; Rodríguez Álvarez, Alicia; Rodríguez Herrera, Gregorio; Trujillo González, Verónica C. (Servicio de Publicaciones y Difusión Científica de la ULPGC, 2016)
Words across History: Advances in Historical Lexicography and Lexicology is a collection of thirty-three essays presenting recent trends, in-depth analyses and corpus-based studies that together attest to the diversity and dynamism currently existing in the domain. The essays result from individual and collective works written by forty-three contributors from seventeen countries, who offer innovative and insightful observations by discussing relevant and up-to-date issues of interest. The volume covers a variety of topics, including the advances in digital and online dictionary-making; the difficulties posed by the representation of special writing systems and accurate pronunciation; the field of specialised terminology and lexicons; the influence of extralinguistic factors in dictionary compilation and editorial decisions; the interrelation of gender studies and lexicography/lexicology; the presence of authorities and sources of dictionaries; some new dictionary projects that complement traditional proposals; as well as diverse works related to etymology, regional forms, word formation or the relationship between lexicon and language-in- use.